Enhancement of apple (Malus domestica) productivity and soil health through organic fertilization and bio-inoculants under north-western Himalayan region of India - KUMAR, SARVENDRA; SHARMA, ANIL; SHARMA, V K; ROSIN, K G; KUMAR, DINESH (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was performed to assess the medium-term effect of mineral fertilizer and organic fertilizer (vermicompost) supplemented with microbial inoculants (Azotobacter and Microphos) on growth parameters of apple (Malus domestica Borkh. cv. Oregon Spur) and soil health parameters. Eight different combinations of mineral fertilizer, vermicompost (VC) and microbial inoculants treatments were applied during 2012 to 2014. The percentage increase in trunk cross section area (TCSA) during the three years of experiment was maximum 17.0% and 15.8% with application of 75% of recommended dose of fertilizer (RDF) + 25% N through VC + Microphos and 50% of RDF + 50% N through VC, respectively. The pooled data of three years revealed that, maximum fruit yield (20.8 tonnes/ha) and production efficiency (112 g/cm2 TCSA) of crop were recorded in the treatment received 50% N through VC and this treatment is similar (P â‰¤ 0.05) with treatment having application of 75% of RDF + 25% N through VC + Microphos while minimum was recorded in control. Among all treatments, application of 50% N through VC and application of 25% N through VC + Microphos performed better for taming chemical fertility of soil. Study also noticed that, continuous three years application of 50% N through VC, the soil organic carbon, soil microbial biomass carbon and dehydrogenase activity of soil increased by 17, 33 and 39%, respectively over control. Overall, study revealed that, plants received 50% of RDF + 50% VC or 25% VC + Microphos had highest ability of promoting the sustainability of apple yield, soil biological and chemical fertility of an agro-ecosystem in north-western Himalayan region.